Learning Loss Typology: A Proposed Framework for Categorizing Learning Loss During COVID-19 Pandemic - Pratama, Putu Yoga Sathya; Nitiasih, Ni Putu Kerti; Suwastini, Ni Komang Arie (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2023)
Learning loss has been a global issue around educational scope lately. This study aimed at proposing a framework for categorizing learning loss during the covid-19 pandemic based on article review results. A qualitative approach has been employed utilizing systematic and qualitative-critical reviews as the research design. The main subject involved 26 articles that were selected purposively. All data were analyzed interactively before the objective was set, and the results were portrayed through grounded theory by Anderson & Krathwohl's dimensions of learning. The results show that learning loss in the affective domain includes a lack of learning motivation, social interaction, self-esteem, engagement, and interest. The sources of learning loss in the affective domain are geographical factors, socio-economic factors, and the digital divide; and in the psychomotor domain are educational inequality and low competence to adapt to situations. The mitigation of learning loss in the affective domain is improving learning facilities and mental care for students in the cognitive domain is adjusting the curriculum and adapting learning methods; in the psychomotor domain is an enhancing literacy skill.